Theoretical bio-investigation of 3-(benzo[d]thiazol-2-yl)-2-(substituted aryl)thiazolidin-4-one derivatives as potential Mycobacterium tuberculosis H37Rv inhibitors - Oke, David Gbenga; Olalekan, Olamide Adetunji; Olujinmi, Eniola Faith; Aworinde, Juliana Oluwasayo; Oyebamiji, Abel Kolawole (Eclética Química, 2025)
3-(Benzo[d]thiazol-2-yl)-2-((substituted aryl) thiazolidin-4-one derivatives were recently synthesized with thioglycolic acid and evaluated for in vitro anti-tubercular activity. Two of the derivatives have good anti-tubercular activity. The present study evaluated an in-silico investigation of these ten novel compounds as potential Mycobacterium tuberculosis H37Rv inhibitors. The non-bonding interactions between the derivatives and the receptor were studied. Spartan ‘14 software was used for optimization. Discovery Studio software was used for the receptor treatment. The binding site in the downloaded protein was located using Autodock Tool software. Auto Dock Vina was used to calculate the docking, and Discovery Studio was used to view the non-bonding interactions between the docked complexes. Different other parameters were calculated to describe anti-tubercular activities of 3-(benzo[d]thiazol-2-yl)-2-(substituted aryl)thiazolidin-4-one derivatives. The findings demonstrated the potential anti-tubercular properties of all the substances under study and inhibited Mycobacterium tuberculosis (H37Rv). The calculated binding affinity of the docked compound showed improved inhibition against Mycobacterium tuberculosis (H37Rv) better than the standard drugs (Streptomycin and Pyrazinamide), with compound 6 being the best.